2018
DOI: 10.17743/jaes.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Listener Preference for Wave Field Synthesis, Stereophony, and Different Mixes in Popular Music

Abstract: Stereophony and wave field synthesis are capable of providing the listener with a rich spatial audio experience. They both come with different advantages and challenges. A direct comparison in terms of listener preference has rarely been carried out in previous research, since these methods differ in their production stage. This study generated mixes of four different popular music recordings and introduced systematic changes to the wave field synthesis mix for one song. Listeners rated their preference compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…Some participants based their preference mostly on the content, while others on the system used for reproduction. Similar trends for OLE were also found from evaluations of 3D audio systems [4] and from comparisons of different reproduction systems [5,6]. In a previous work of the authors [21], a simple regression model for OLE prediction of binaurally recorded music excerpts in three different formats (mono, stereo and surround) was introduced and the results indicated that it is the preference for the content of the music excerpts that dominated on OLE formation, whilst a lesser impact was registered by the perceptual factors (in this case only Envelopment was considered) introduced by the audio system.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some participants based their preference mostly on the content, while others on the system used for reproduction. Similar trends for OLE were also found from evaluations of 3D audio systems [4] and from comparisons of different reproduction systems [5,6]. In a previous work of the authors [21], a simple regression model for OLE prediction of binaurally recorded music excerpts in three different formats (mono, stereo and surround) was introduced and the results indicated that it is the preference for the content of the music excerpts that dominated on OLE formation, whilst a lesser impact was registered by the perceptual factors (in this case only Envelopment was considered) introduced by the audio system.…”
Section: Introductionsupporting
confidence: 78%
“…As with many other aspects of audio system performance, a growing body of recent research concerns methods that can also describe and predict the listener's experiences incorporating individual preferences for the content, i.e. the music material [4][5][6].…”
Section: Introductionmentioning
confidence: 99%